Unveiling toxic masculinity symbols: Peircean semiotic analysis in films “Seperti Dendam Rindu Harus Dibayar Tuntas” - Widiasa, Damarati Rahma; Mahdalena, Vina; Handayani, Lusia (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2023)
“Seperti Dendam Rindu Harus Dibayar Tuntas” movie depicts how societal pressures concerning masculine characters are illustrated through male attractiveness, centered around their genitalia, the dominance of power, the suppression of emotions or sadness, and physical strength and toughness. According to Terry A. Kupers, toxic masculinity comprises four main components: the suppression of anything labeled as feminine, emotional repression, male domination, and aggression. This study employs a qualitative and descriptive approach to illustrate the phenomenon of toxic masculinity in films. The data collection is conducted through documentary, observational, and literary methods and subsequently analyzed using Peirce's semiotics by examining icons, indexes, and symbols. The research results demonstrate that the representation of toxic masculinity in the film is portrayed through Ajo Kawir as the main character who suffers from impotence and adopts masculine traits to mask his condition. Toxic masculinity behavior is more likely to be produced when Ajo Kawir's masculinity is threatened. Ajo's toxic masculinity behavior becomes more extreme after experiencing erectile dysfunction. Furthermore, this research reveals that sexual power is a part of toxic masculinity, depicted by viewing male genitalia as a symbol of virility. Related to the characteristics of toxic masculinity, this research identifies a complementary character in Kupers' concept, which is excessive sexual processes.